Nanomaterials for bioprinting: functionalization of tissue-specific bioinks. Issue 3 (10th August 2021) - Theus, Andrea S.; Ning, Liqun; Jin, Linqi; Roeder, Ryan K.; Zhang, Jianyi; Serpooshan, Vahid
Abstract: Three-dimensional (3D) bioprinting is rapidly evolving, offering great potential for manufacturing functional tissue analogs for use in diverse biomedical applications, including regenerative medicine, drug delivery, and disease modeling. Biomaterials used as bioinks in printing processes must meet strict physiochemical and biomechanical requirements to ensure adequate printing fidelity, while closely mimicking the characteristics of the native tissue. To achieve this goal, nanomaterials are increasingly being investigated as a robust tool to functionalize bioink materials. In this review, we discuss the growing role of different nano-biomaterials in engineering functional bioinks for a variety of tissue engineering applications. The development and commercialization of these nanomaterial solutions for 3D bioprinting would be a significant step towards clinical translation of biofabrication.